Design and Optimization of PMSM by Using the Thermal Behaviour of Fluid Dynamics - Radhika, S.; Marsalin Beno, M.; Jaikumar, R. A. (Asian Journal of Electrical Sciences, 2015)
One of the efficient gadgets possessing magnificent scope for the enhancement of energy efficiency is the electrical motor. Amid, several kinds of electrical motors, Permanent magnet synchronous motors are widely employed in countless sophisticated applications. This phenomenon has enabled it to be shortlisted for our investigation, which predominantly centres on the thermal character of the Permanent Magnet Synchronous Motor (PMSM), which is designed and replicated in a Computational Fluid Dynamics Software ANSYS FLUENT-13. The heat transfer inside the motor is assessed for diverse functional constraints like inlet velocity, ambient temperature, air gap thickness, heat flux, and convective heat transfer coefficient. The optimum conditions to be preserved to perk up the heat dissipation pace and to dwindle down the highest temperature are forecast. It is pertinent to note that the forecasts from the analyses closely resemble those gathered from literary community, thereby authenticating the aptness of the assessment.